Komunikasi Persuasif Iklan Pinjaman Online AdaKami di TikTok: Analisis Respons Komentar Pengguna - Wijaya, Cahyo; Kurniawan, Firdaus Dwi Cahyo (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
Social media has become an important tool in digital marketing, including the promotion of online lending services. TikTok, with a large user base in Indonesia, is utilized by fintech companies such as AdaKami to deliver persuasive advertisements emphasizing ease of use, fast fund disbursement, and unsecured services. This study aims to analyze persuasive communication strategies in TikTok advertising content on the @Adakami_Official account and to examine user responses through the comment section. The research employs a descriptive qualitative approach, using advertising videos and user comments as data, which are analyzed based on persuasive communication theory. The findings indicate that AdaKami’s advertisements predominantly use the peripheral route through visual appeal, persuasive phrasing, and a sense of urgency. User responses vary, ranging from positive comments regarding service convenience to negative feedback highlighting interest rates and loan risks. The study concludes that persuasive communication in digital advertising is effective in shaping public opinion but may lead to perceptual bias if information is not presented transparently.